2021
DOI: 10.3390/v13060983
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Epitope Immunodominance and B Cell Repertoire Diversity

Abstract: Despite the advent of effective, curative treatments for hepatitis C virus (HCV), a preventative vaccine remains essential for the global elimination of HCV. It is now clear that the induction of broadly neutralising antibodies (bNAbs) is essential for the rational design of such a vaccine. This review details the current understanding of epitopes on the HCV envelope, characterising the potency, breadth and immunodominance of antibodies induced against these epitopes, as well as describing the interactions bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…The HCV envelope protein E1E2 with the different domains (Dom) and/or antigenic regions (AR) targeted by specific monoclonal antibodies used for epitope mapping of plasma anti‐E2 antibodies produced by patients is shown in Figure 6A for reference 30 . A statistical correlation matrix showed that antibodies in patient plasma targeting E2 Domain B (AR3A) and Domain D (HC84.26) had a significant positive relationship with high phagocytosis with r scores of 0.64 ( p = 0.0001) and 0.51 ( p = 0.0003), respectively, as contrasted to the significant negative relationships observed between high phagocytosis and antibodies targeting E2 Domain E (HCV1) and Domain C (CBH‐7) with r scores of −0.38 ( p = 0.008) and −0.36 ( p = 0.0003), respectively, (Figure 6B).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The HCV envelope protein E1E2 with the different domains (Dom) and/or antigenic regions (AR) targeted by specific monoclonal antibodies used for epitope mapping of plasma anti‐E2 antibodies produced by patients is shown in Figure 6A for reference 30 . A statistical correlation matrix showed that antibodies in patient plasma targeting E2 Domain B (AR3A) and Domain D (HC84.26) had a significant positive relationship with high phagocytosis with r scores of 0.64 ( p = 0.0001) and 0.51 ( p = 0.0003), respectively, as contrasted to the significant negative relationships observed between high phagocytosis and antibodies targeting E2 Domain E (HCV1) and Domain C (CBH‐7) with r scores of −0.38 ( p = 0.008) and −0.36 ( p = 0.0003), respectively, (Figure 6B).…”
Section: Resultsmentioning
confidence: 99%
“…The HCV envelope protein E1E2 with the different domains (Dom) and/or antigenic regions (AR) targeted by specific monoclonal antibodies used for epitope mapping of plasma anti‐E2 antibodies produced by patients is shown in Figure 6A for reference. 30 A statistical correlation matrix showed that antibodies in patient plasma targeting E2 Domain B (AR3A) and Domain D (HC84.26) had a significant positive relationship with high phagocytosis with r scores of 0.64 ( p = 0.0001) and 0.51 ( p = 0.0003), respectively, as contrasted to the significant negative relationships observed between high phagocytosis and antibodies targeting E2 Domain E (HCV1) and Domain C (CBH‐7) with r scores of −0.38 ( p = 0.008) and −0.36 ( p = 0.0003), respectively, (Figure 6B ). Interestingly, antibodies targeting Domains B and D had also a significant positive association to neutralization function with r scores of 0.65 ( p = 0.0001) and 0.53 ( p = 0.0004), respectively, while those targeting Domains E ( r = −0.33; p = 0.03) and Domain C ( r = −0.58; p = 0.0004) had significant negative associations, suggesting functional overlap between ADCP and neutralization (Figure 6C ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations